Contemporary avenues in catalytic P-H bond addition reaction: a case study of hydrophosphination - Koshti, Vijay; Gaikwad, Shahaji R.; Chikkali, Samir H. (Coordination Chemistry Reviews, 2014)
Remarkable advances and current state-of-the-art developments in catalytic hydrophosphination of alkenes and alkynes are reviewed. The challenges in constructing a C P bond with a special emphasis on metal catalysed (asymmetric) hydrophosphination are highlighted. Only those systems that unambiguously proceed via P H bond addition across a C-C/X (X = O, N, S) multiple bond have been covered in this overview. Reviewed examples support the assumption that either strongly chelating ligands or reaction products that act as ligands, enhance the rate of hydrophosphination. The asymmetric variant of this transformation allows installation of p-chiral [enantiomeric excess (ee) up to 82%] as well as C-chiral (ee up to 99%) centres. The limited spectroscopic, mechanistic data and OFT calculations point at two distinctly different mechanisms. In case of hydrophosphination, the metal undergoes oxidative addition and reductive elimination steps (in general), thus changing the oxidation state from M(0) to M(II) and back to M(0). Whereas in asymmetric hydrophosphination it is proposed that the oxidation state of the metal remains unaltered throughout the catalytic cycle. The examples described in this overview showcase the real power of catalytic hydrophosphination in constructing various phosphorus compounds, which may initiate a new era in organo-phosphorus chemistry. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Alkynes; Asymmetric hydrophosphination; Hydrophosphination; Metal catalyzed hydrophosphination; Olefins; P-H bond addition